A Sports Analogy for Understanding Different Ways to Use AI - Hofman, Jake; Goldstein, Daniel G.; Rothschild, David (Harvard Business Review, 2023)
The potential impact of generative AI on the economy, society, and work is polarizing, swinging from the positive benefits of a technological revolution to doomsday scenarios. The authors have come to think about this issue as points on a spectrum and have created a sports analogy to help think about it: AI tools can range from steroids, to sneakers, to a coach, each representing a different relationship between human users and the technology. Steroids elevate short-term performance, but leave you worse off in the long term. AI-powered tools can instead be used to augment people’s skills and make them more productive — much like a good running sneaker. On the most desirable end of the spectrum, AI-powered tools can be used like a coach that improves people’s own capabilities. This framework can be used to help conceptualize how we might craft AI-based tools that enhance rather than diminish human capabilities.